Between Logic of Blessing and Accounting Rationality: Financial Reporting Formalization Process in a Sharia Property Developer - Icha Mustamin; Alimuddin; Darwis Said (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This research explores the meaning of accountability and the fundamental challenges arising during the transition from a manual reporting system to a formal accounting system in a non-bank Islamic property developer. Utilizing a qualitative approach with an in-depth design, the researcher served as a participant-observer for over five months at PT. Pandawa Lima Development in South Sulawesi. Data collection involved triangulation of semi-structured interviews, participant observations, and document analysis to ensure validity. The findings identify the existence of a